Association among knowledge on infant and young child feeding recommendations, dietary fat content of complementary foods, and complementary feeding practices of mothers of children with down syndrome aged 6 to 23 months - Alforte, Selina D.; Esteban, Charlene Denise S.; Superal, Hanazel B. (University of the Philippines Diliman, 2023)
Malnutrition among children aged 6-23 months remains a prevalent problem locally and globally. With disease-specific oral-motor problems and feeding difficulties, children with Down Syndrome (DS) are at an even higher risk. Hence, appropriate complementary feeding (CF) practices are essential in achieving adequate nutrition. This study aimed to determine whether maternal knowledge on infant and young child feeding (IYCF) recommendations were associated with the CF practices of mothers and the dietary fat – specifically, polyunsaturated fatty acid (PUFA) – content of complementary foods given to children. The study included 10 mothers of children with DS aged 6-23 months from low-income families. IYCF knowledge was assessed through a self-administered questionnaire, while maternal CF practices characterized by indicators Minimum Dietary Diversity (MDD) and Minimum Meal Frequency (MMF) was determined through an interviewer-administered questionnaire. Lastly, the dietary fat content of complementary foods was measured through a 2-day multiple pass 24-hour food recall. Participants were found to have average (n=7) to high (n=3) knowledge of IYCF recommendations. The achievement of MDD and MMF among the children was low at 40% for both. Maternal IYCF knowledge is directly associated with MDD (Tb = 0.3563), inversely associated with MMF (Tb=-0.5345), and weakly associated with PUFA content (Tb=0.0976). However, these relationships were not significantly correlated with p-values of α=0.2850, α=0.1088, α=0.7324, respectively. On the other hand, the overall dietary fat content of the children’s diet was strongly associated with their intake of total PUFA (ρ=0.7697; α=0.0092), omega-3 (ρ=0.6832; α=0.0294), and omega-6 fatty acids (ρ=0.7091; α=0.0217). This implies that as children consumed dietary fat as a common component of CF, they were also able to consume PUFA which is essential for brain function and development especially for children with DS. Further studies are recommended to increase sample size and explore other nutritional aspects of feeding infants and young children with DS.